2017
DOI: 10.3847/1538-4357/aa7949
|View full text |Cite
|
Sign up to set email alerts
|

Saraswati: An Extremely Massive ∼200 Megaparsec Scale Supercluster

Abstract: Here we report the discovery of an extremely massive and large supercluster (called Saraswati a) ) found in the Stripe 82 region of SDSS. This supercluster is a major concentration of galaxies and galaxy clusters, forming a wall-like structure spanning at least 200 Mpc across at the redshift z ≈ 0.3. This enormous structure is surrounded by a network of galaxy filaments, clusters, and large, ∼ 40−170 Mpc diameter, voids. The mean density contrast δ (relative to the background matter density of the universe) of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 59 publications
4
41
0
1
Order By: Relevance
“…Cluster mergers are highly dynamical processes (Sarazin 2002), and numerous, heterogeneous merger episodes (Ferrari et al 2006;Poole et al 2006) are considered to be the most natural physical processes for disturbing both their cool-core and relaxed structure. Even in the present age, clusters are constantly growing by matter accretion at the nodes of large scale filaments of galaxies (Springel et al 2005;Dolag et al 2008;Tempel et al 2014;Bagchi et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Cluster mergers are highly dynamical processes (Sarazin 2002), and numerous, heterogeneous merger episodes (Ferrari et al 2006;Poole et al 2006) are considered to be the most natural physical processes for disturbing both their cool-core and relaxed structure. Even in the present age, clusters are constantly growing by matter accretion at the nodes of large scale filaments of galaxies (Springel et al 2005;Dolag et al 2008;Tempel et al 2014;Bagchi et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, up to now a few Great Walls have been reliably established, and their number is constantly growing. These are the CfA Great Wall [56], Sloan Great Wall [57,58], BOSS Great Wall [59] and Saraswati wall-like structure [60]. One can also refer to such objects as the supergalactic plane [61] in the local Universe, as well as the Sharpley Supercluster (e.g., [62,63]), and the recently revealed South Pole Wall [64].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In this regard, the question arises about the largest allowable scales of cosmological structures (huge superclusters and voids between them) consistent with the generally accepted ΛCDM cosmological model (e.g., [60]) with its extensive observation base. A possible answer to this question was given in [65], where it was shown that the largest structures of relatively low density can reach several hundred Megaparsecs without conflicting with the isotropy and uniformity of the ΛCDM model.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In this paper, we show the importance of the third-generation calibration (3GC, [11]) on wide field-of-view (FOV) radio interferometry observations, for example, the Saraswati supercluster [12]. In radio astronomy, subsequent developments in calibration and imaging techniques have enhanced our knowledge of the radio universe.…”
Section: Introductionmentioning
confidence: 99%